2016
DOI: 10.1016/j.canep.2016.10.008
|View full text |Cite|
|
Sign up to set email alerts
|

The burden of HPV associated cancers in two regions in Nigeria 2012–2014

Abstract: Introduction HPV attributable cancers are the second most common infection-related cancers worldwide, with much higher burden in less developed regions. There are currently no country-specific estimates of the burden of these cancers in Nigeria just like many other low and middle income countries. Methods In this study, we quantified the proportion of the cancer burden in Nigeria that is attributable to HPV infection from 2012 to 2014 using HPV prevalence estimated from previous studies and data from two pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…The included studies comprise of review articles which made the bulk of the articles with 77.7% (7/9) [90][91][92][93][94][95][96] and (1/9) transversal case control study [97] and (1/9) quantitative study [98] and each contributed 11.1% respectively.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies comprise of review articles which made the bulk of the articles with 77.7% (7/9) [90][91][92][93][94][95][96] and (1/9) transversal case control study [97] and (1/9) quantitative study [98] and each contributed 11.1% respectively.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The studies were done and reviewed from different study settings. About 11.1% (1/9) study generalized about SSA with no specific country mentioned [90], 44% (4/9) reported about Uganda [91,92,95,96], 33% (3/9) South Africa (SA) [93,95,96], 22% (2/9) Senegal [94,96], (1/9) Zambia [93], (1/9) Nigeria [98], and (1/9) Benin [97], and each contributed 11% respectively. Among the included studies, only three were conducted in an urban setting; those of the rest of the studies were not mentioned.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations